Tantangan Madrasah Daerah 3T dalam Menghadapi Masyarakat 5.0 - Fahmi Astathi (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2023)
This research aims to describe all the challenges in madrasahs located in 3T areas (Disadvantaged, Frontier and Outermost) in facing social society era 5.0. as well as strategies used to face social society era 5.0. The method used is qualitative in the form of a case study and presented descriptively. The results of this research show that the challenges found in facing social society in the 5.0 era in madrasas located in 3T areas originate from several factors including the madrasa environment or geographic location of an area, educator or teacher factors, and factors originating from students or students. The geographic location of an area influences electricity stability. Challenges that come from teachers or educators come from a lack of insight regarding social society in the 5.0 era, and challenges that come from students, namely students' socio-economics and motivation to accept new things along with the times.